Discussion of The Incremental Information Content of Financial Statement Disclosures: The Case of LIFO Inventory Liquidations - Pincus, Morton (Journal of Accounting Research, 1986)
Morton Pincus, Discussion of The Incremental Information Content of Financial Statement Disclosures: The Case of LIFO Inventory Liquidations, Journal of Accounting Research, Vol. 24, Studies on Alternative Measures of Accounting Income (1986), pp. 161-164